Evidence of exposure to organophosphorus toxicants by detection of the propionylated butyrylcholinesterase-derived nonapeptide-adduct as a novel biomarker. (June 2021) - John, Harald; Richter, Annika; Siegert, Markus; Eyer, Florian; Thiermann, Horst
Abstract: Organophosphorus (OP) nerve agents represent a class of highly toxic chemical warfare agents banned by the Chemical Weapons Convention. Nevertheless, in the past few years they have been used repeatedly for warfare, assassination and attempted murder. In addition, the chemically related OP pesticides were frequently used for suicide and may be deployed for terroristic attacks. Therefore, sensitive and selective bioanalytical methods are indispensable to investigate biological specimens as pieces of evidence to prove poisoning. OP agents form long-lived covalent reaction products (adducts) with endogenous proteins like human serum albumin (HSA) and butyrylcholinesterase (BChE). The adducted nonapeptide (NP) obtained by proteolysis of the BChE-adduct is one of the most sensitive and important biomarkers. We herein present a novel class of NP-adducts propionylated at its N-terminal phenylalanine residue (F 195 ). The biomarker derivative is produced by addition of propionic anhydride to the NP-adduct inducing its quantitative conversion in aqueous buffer within 5 min at room temperature. Afterwards the mixture is directly analyzed by micro-liquid chromatography-electrospray ionization tandem-mass spectrometry (µLC-ESI MS/MS). The sensitivity of the method is comparable to that of the non-derivatized NP-adduct. These characteristics make the method highly beneficial for forensic analysis especially in cases in which the OP agent does not form adducts with HSA that are typically targeted as a second biomarker of exposure. This novel procedure was successfully applied to nerve agent-spiked samples sent by the Organisation for the Prohibition of Chemical Weapons (OPCW) as well as to plasma samples of real cases of pesticide poisoning.